1988
DOI: 10.1128/aac.32.3.358
|View full text |Cite
|
Sign up to set email alerts
|

Antiherpesvirus activity of 9-(4-hydroxy-3-hydroxymethylbut-1-yl) guanine (BRL 39123) in animals

Abstract: The antiviral activity of 9-(4-hydroxy-3-hydroxymethylbut-1-yl)guanine (BRL 39123) was assessed in several animal models of herpes simplex virus (HSV) infection. BRL 39123 was as active as acyclovir (ACV) when applied topically to guinea pigs with a cutaneous HSV type 1 (HSV-1) infection and was also active topically in an HSV-2 genital infection. Before systemic administration to infected animals, BRL 39123 and ACV were administered orally and subcutaneously to mice, and the blood was assayed for each compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
101
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 19 publications
(20 reference statements)
9
101
0
Order By: Relevance
“…ganciclovir (Smith et al, 1983;Rollinson and White, 1983;Rollinson, 1987), three 2 0 -fluoropyrimidine nucleosides (Rollinson, 1987), (S)-9-[3-hydroxy-2-phosphonylmethoxypropyl]adenine or HPMPA (Field and Awan, 1990) and the HPMPA analogue cidofovir (Gibson et al, 1992). These compounds proved more effective than 9-[4-hydroxy-3-hydroxymethylbut-1-yl]guanine (Boyd et al, 1987) and penciclovir (de la Fuente et al, 1992). For acyclovir, contradictory data have been reported.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…ganciclovir (Smith et al, 1983;Rollinson and White, 1983;Rollinson, 1987), three 2 0 -fluoropyrimidine nucleosides (Rollinson, 1987), (S)-9-[3-hydroxy-2-phosphonylmethoxypropyl]adenine or HPMPA (Field and Awan, 1990) and the HPMPA analogue cidofovir (Gibson et al, 1992). These compounds proved more effective than 9-[4-hydroxy-3-hydroxymethylbut-1-yl]guanine (Boyd et al, 1987) and penciclovir (de la Fuente et al, 1992). For acyclovir, contradictory data have been reported.…”
Section: Introductionmentioning
confidence: 98%
“…For acyclovir, contradictory data have been reported. Rollinson and White (1983) reported a 6-fold lower EC 50 than Boyd et al (1987). Further, based on comparison of EC 50 -values reported in literature, adefovir would be the least active compound in this series (Field and Awan, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Several HSV mutants known to contain ACV-resistance mutations in the pol gene have been examined for PCV susceptibility, but most have been reported to be as sensitive as their wild-type parents (Boyd et al, 1987;. To investigate further whether mutations in the HSV pol gene could confer altered sensitivity to PCV, we studied five drug-resistant mutants known or suspected to contain pol mutations.…”
Section: Susceptibilities Of Hsvpol Mutants To Pcvmentioning
confidence: 99%
“…Perkins, 1989;Hannah et al, 1989;Earnshaw et al, 1992;Vere Hodge and Cheng, 1993) have indicated that, like ACV and GCV, PCV is phosphorylated by the HSV thymidine kinase (TK) to the monophosphate. TK-deficient mutants are resistant to PCV (Larsson et al, 1986;Boyd et al, 1987;, indicating that phosphorylation by TK is critical for the selective antiviral activity of PCV. Once monophosphorylated, cellular enzymes can convert PCV monophosphate to its triphosphate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation